(untitled) (Research, Society and Development, 2022)
To reflect on aspects of clinical nursing care for premature in the context of the kangaroo unit and its contribution to the prevention of early weaning. Integrative literature review, carried out from August to September 2019, in the following bases: VHL; PubMed via MedLine; Scielo and LILACS, using the search equation: premature newborn AND family relationships AND breastfeeding. The data were organized in a flowchart and table, later the studies were analyzed in a reflective way. 201 articles were found, but only 10 articles contemplated the search. The context of the Kangaroo Unit and its peculiarities allow the Nurse to understand the bond between the mother-child binomial, broken with premature birth and hospitalization. Among the difficulties that arise in the Kangaroo Unit is breastfeeding, because depending on the length of stay, the mother may have reduced milk production, not meeting the baby’s needs. In the Kangaroo Unit, the support network is not just family, but institutional through the health team that serves the dyad. Perceiving the nursing team as a support network for care and encouraging the practice of breastfeeding becomes the key point to increase breastfeeding rates among premature infants.